A qualitative investigation of the barriers and facilitators to Hepatitis C virus (HCV) screening among individuals experiencing homelessness in Houston, Texas - Alane Celeste-Villalvir; J. Michael Wilkerson; Christine Markham; Lourdes Rodriguez; Vanessa Schick (Elsevier, 2022)
Background. Individuals experiencing homelessness may be at a higher risk for hepatitis C infection because many are vulnerable to risk factors related to HCV. Screening is the very first step in the HCV care continuum, but it remains unclear how to improve HCV screening among this hard-to-reach population. Thus, the present study investigated the barriers and facilitators to HCV screening from the perspective of individuals experiencing homelessness within a non-residential social service setting. Methods. Individuals experiencing homelessness (aged 18+) were approached while they were seeking services at two community-based organizations in Houston, Texas, during August 2020. Participants (N = 31) completed an interviewer-administered demographic survey and a semi-structured interview about their experiences with healthcare, homelessness, and HCV screening. Following transcript coding and content analysis, a thematic analysis was conducted to identify HCV screening barriers and facilitators discussed by participants. Results. Participants were predominantly male (n = 25, 80.6%), and almost 40% of participants had no form of medical insurance. Participants identified the following as barriers to HCV screening: mistrust of the healthcare system and professionals and lack of knowledge of HCV prevention, harm reduction, and complications. Participants identified the following as facilitators to HCV screening: providing incentives and increasing access and convenience to HCV screening. Conclusion. Community-based HCV screening programs may wish to account for the lived experiences of individuals experiencing homelessness in order to minimize barriers to screening. Client-centered strategies that reduce wait times and incentivize participation should be considered to eliminate barriers and increase convenience for this high-risk population.